Changing Money Viewed From Positive Law and Islamic law - Muhammad Arifin (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Hasil Penilaian Peer Review Changing Money Viewed From Positive Law and Islamic la